Titanium alloy based on laser energy density to control phase structure and preparation method thereof

By regulating the laser energy density and controlling the α phase in the titanium alloy, the problem of poor plastic toughness in the laser melting, deposition and forming process is solved, and the alloy structure of balanced strength and plasticity is achieved.

CN118703913BActive Publication Date: 2025-02-21ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411205037.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-02-21
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

Titanium alloys are prone to form fine needle-shaped α′martensite structure during laser melting, deposition and forming, resulting in poor plastic toughness of the material. The existing technology cannot accurately regulate the area proportion of α′martensite structure and cannot obtain strength. and suitable plastic structure.

Method used

By regulating the laser energy density, the morphology of the α phase in the titanium alloy is controlled, and the transformation from needle-shaped α′martensite to the slat and near-equiaxed α phases is achieved to achieve a balanced alloy structure of strength and plasticity.

Benefits of technology

The mechanical properties of the titanium alloy are optimized as needed, and the structure with suitable strength and plasticity is obtained, which solves the problem of poor forming performance of titanium alloys in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118703913B_ABST
    Figure CN118703913B_ABST
Patent Text Reader

Abstract

The invention discloses a titanium alloy based on laser energy density regulation of phase structure and a preparation method thereof. The mass percentages of the components of the titanium alloy are Al: 5.54%-6.68%, V: 4.25%-4.48%, Fe: 2.59%-3.04%, B: 0.02-0.08%, and the remainder is Ti; the titanium alloy matrix is ​​mainly composed of α phase and residual β phase, and small-sized TiB whiskers are dispersed in the titanium alloy matrix. The titanium alloy is prepared by laser additive manufacturing, and the laser energy density of the laser additive manufacturing is 33-45 J / mm 2 , 60‑77 J / mm 2 , 90‑109 J / mm 2 , 109‑132 J / mm 2 ; With the increase of laser energy density, the transformation process of the α phase is needle-shaped α′ martensite → needle-shaped α′ martensite + lath-shaped α phase → lath-shaped α phase → nearly equiaxed α phase. The titanium alloy can have better mechanical properties and more matched strength and plasticity based on the regulation of laser energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of metal alloys, and in particular relates to a titanium alloy with phase structure regulated based on laser energy density and a preparation method thereof. Background Art

[0002] Titanium alloys are widely used in aerospace due to their low density, high yield strength and good corrosion resistance. However, titanium alloys have poor thermal conductivity and thus poor forming properties. Its processing and manufacturing performance has always been the focus and difficulty of research at home and abroad. Laser additive manufacturing technology is a new manufacturing technology developed in recent years. It integrates manufacturing and forming. It can directly manufacture large-scale complex three-dimensional titanium alloy structures at the same time, and can greatly reduce the amount of mechanical processing, reduce production costs, shorten the manufacturing cycle, and improve material utilization. In particular, it can directly form some complex and high-performance titanium alloy structures, showing great potential in the application of aerospace structures.

[0003] TC4 (Ti-6Al-4V) is a dual-phase titanium alloy with good comprehensive properties. It accounts for about 45% of the total titanium alloy and is currently the most widely used titanium alloy material. In the aviation field, it can be used for a variety of parts such as beams, bulkheads, slide rails, landing gear beams, and engine fans and compressor discs, blades, etc., and has important application value. The direct preparation of TC4 aviation structural parts using laser additive manufacturing technology has also attracted the attention of many researchers. Although the laser direct forming process is simple and the cost is reduced, one-time forming will cause the material to face more serious mechanical properties problems in the end.

[0004] The invention patent application with publication number CN110983106A discloses a method for inhibiting the formation of needle-shaped martensite phase in 3D printed TC4 alloy structure. TC4 powder is formed by laser melting deposition on a TC4 alloy plate substrate to obtain a TC4 titanium alloy material whose shape meets the requirements; the obtained TC4 titanium alloy material is separated from the substrate by wire cutting technology to obtain a TC4 alloy material whose plasticity and toughness meet the use requirements. The method of the present invention mainly solves the problem that TC4 titanium alloy is prone to obtain fine needle-shaped α' martensite structure during laser melting deposition forming, resulting in poor plasticity and toughness of the material. However, the method disclosed in the patent cannot accurately control the area ratio of α' martensite structure, so that it is impossible to obtain a TC4 alloy structure with suitable strength and plasticity as required.

[0005] The invention patent application with publication number CN112251640A discloses a nanocrystalline Ti6Al4V-Ag alloy and its additive manufacturing preparation method. The chemical composition of the alloy is as follows (weight %): Ag: 0.1-10.5; Al: 5.5-6.5; V: 3.5-4.5; the balance is Ti. The preparation method of the nanocrystalline Ti6Al4V-Ag alloy is: using selective laser melting technology, laser power 200-400 W, scanning speed 800-1500 mm·s -1 , interlayer deflection angle 10-60°, energy density 50-150 J·mm -3 The microstructure of the prepared material is a nano-lath structure, and the width of the lath structure is between 20-150 nm. However, the method disclosed in the patent cannot accurately determine the area ratio of the nano-lath structure, and thus cannot obtain a TC4 alloy structure with suitable strength and plasticity as required.

[0006] The cooling rate of TC4 (Ti-6Al-4V) alloy printed by laser additive manufacturing technology is too fast, which makes the alloy structure easy to form coarse columnar crystals along the printing direction, and α′ needle-shaped martensite is precipitated in the crystal, which can improve the strength of the alloy, but greatly reduce the toughness of the alloy; secondly, the layer-by-layer laser scanning mode will cause layer-by-layer heat accumulation, which will cause the solidified structure of the bottom layer of the alloy to be repeatedly heated and cooled rapidly, and multiple solid-state phase changes will occur. The heat accumulation of the upper layer of the alloy is serious, the phase structure is coarser, and the microstructure and mechanical properties are uneven along the printing direction. Specifically, the additively manufactured TC4 alloy has low strength, it is difficult to coordinate strength and plasticity, and the structure and performance are anisotropic along the printing direction. Summary of the invention

[0007] The present invention provides a titanium alloy with a phase structure regulated based on laser energy density. The titanium alloy can have good mechanical properties and relatively matched strength and plasticity based on the regulation of laser energy density.

[0008] The present invention provides a titanium alloy based on laser energy density to regulate phase structure, wherein the mass percentages of the components of the titanium alloy include Al: 5.54%-6.68%, V: 4.25%-4.48%, Fe: 2.59%-3.04%, B: 0.02-0.08%, and the balance is Ti;

[0009] The titanium alloy matrix is ​​mainly composed of α phase and residual β phase. The titanium alloy is obtained by laser additive manufacturing. Under different laser energy densities, the α phase includes needle-shaped α′ martensite, needle-shaped α′ martensite + lath-shaped α phase, lath-shaped α phase or nearly equiaxed α phase.

[0010] The α phase provided by the present invention presents different forms under different laser energy densities, thereby obtaining the required strength and plasticity.

[0011] Preferably, as the laser energy density increases, the α phase undergoes the following changes in sequence:

[0012] Needle-shaped α′ martensite → needle-shaped α′ martensite + lath-shaped α phase → lath-shaped α phase → nearly equiaxed α phase.

[0013] Preferably, when the laser energy density is 33-45 J / mm 2 When , the α phase is mainly composed of needle-shaped α′ martensite;

[0014] When the laser energy density is 60-77 J / mm 2 When the α phase includes needle-shaped α′ martensite and lath-shaped α phase, the area ratio of the needle-shaped α′ martensite to the lath-shaped α phase is 0.21-0.39;

[0015] When the laser energy density is 90-109 J / mm 2 When , the α phase is mainly composed of lath-shaped α phase;

[0016] When the laser energy density is 109-132 J / mm 2 When α phase is mainly composed of nearly equiaxed α phase.

[0017] Under different ranges of laser energy density, the α phase morphology and size of the titanium alloy provided by the present invention will be different. Under a specific laser energy density, the α phase of the titanium alloy provided by the present invention will form its corresponding phase structure, thereby obtaining corresponding mechanical properties, and then the required strength and plasticity can be easily obtained by utilizing the corresponding relationship provided by the present invention.

[0018] When the laser energy density is 60-77 J / mm 2 When the energy density is close to the upper limit, the lath-shaped α phase accounts for a higher proportion. When the energy density is close to the upper limit, the needle-shaped α′ martensite content will be higher, the strength will be higher, and the plasticity will be lower. When the energy density is close to the lower limit, the needle-shaped α′ martensite content will be less, the strength will be lower, and the plasticity will be higher.

[0019] Preferably, the laser energy density is 33-45 J / mm 2 , the strength of the titanium alloy is 1592-1610 MPa, and the plasticity of the titanium alloy is 3.4-3.9%;

[0020] The laser energy density is 60-77 J / mm 2 , the strength of the titanium alloy is 1502-1574 MPa, and the plasticity of the titanium alloy is 4.8-5.6%;

[0021] The laser energy density is 90-109 J / mm 2 , the strength of the titanium alloy is 1324-1415 MPa, and the plasticity of the titanium alloy is 9.4-11.7%;

[0022] The laser energy density is 109-132 J / mm 2 The strength of the titanium alloy is 1359-1451 MPa, and the plasticity of the titanium alloy is 11.1-11.7%.

[0023] When the energy density is between 33-45 J / mm 2 、60-77 J / mm 2 、90-109 J / mm 2 When the gradient increases in the three intervals, the strength of the titanium alloy provided by the present invention decreases gradually and the plasticity increases gradually during the transformation from the needle-shaped α′ martensite to the lath-shaped α phase. 2 Increased to 109-132 J / mm 2 When the α phase is nearly equiaxed, the strength and plasticity changes are not obvious.

[0024] Preferably, the laser energy density is 33-45 J / mm 2 , the thickness of the α phase is 55-91 nm;

[0025] The laser energy density is 60-77 J / mm 2 , the thickness of the α phase is 78-182 nm;

[0026] The laser energy density is 90-109 J / mm 2 , the thickness of the α phase is 175-285 nm;

[0027] The laser energy density is 109-132 J / mm 2 , the thickness of the α phase is 203-328 nm.

[0028] As the laser energy density increases, the α phase changes, and the thickness of the α phase increases from a smaller size to a larger size, and the size continues to increase. When the α phase changes from a lamellar α phase to a nearly equiaxed α phase, the increase in the thickness of the α phase decreases, and the length of the nearly equiaxed α phase is relatively small, which is also the reason why the energy density increases from 90-109 J / mm 2 Increased to 109-132 J / mm 2 The reason why the mechanical properties are relatively close.

[0029] Further preferably, when the laser energy density is 40 J / mm2 When the average thickness of the α phase in the alloy is 70 nm, the α phase is mainly composed of needle-shaped α′ martensite phase. At this time, the tensile strength of the alloy is 1592 MPa, and the plastic elongation at fracture is 3.4%, which greatly improves the strength of the alloy.

[0030] The laser energy density is 68 J / mm 2 When the average thickness of the α phase in the alloy is 127 nm, the α phase is composed of needle-shaped α′ martensite phase and lath-shaped α phase. At this time, the tensile strength of the alloy is 1527 MPa, and the plastic elongation at fracture is 5.3%. The alloy has high strength and appropriate plasticity.

[0031] Laser energy density is 100 J / mm 2 When the average thickness of the α phase in the alloy is 197 nm; the α phase is mainly composed of lath-shaped α phase, the tensile strength of the alloy is 1411 MPa, and the plastic elongation at fracture is 11.6%;

[0032] Laser energy density is 120 J / mm 2 When the alloy is oxidized to a high temperature, the average thickness of the α phase in the alloy is 233 nm, and the α phase is mainly composed of nearly equiaxed α phase. At this time, the tensile strength of the alloy is 1453 MPa, and the plastic elongation at fracture is 11.1%, which greatly improves the matching problem of strength and plasticity of the alloy.

[0033] Preferably, the titanium alloy has a basket structure and includes in-situ self-generated short rod-shaped TiB whiskers, the size of which is less than 1 μm and which are randomly dispersed in the initial β crystals and at the grain boundaries.

[0034] Further preferably, the area ratio of the short rod-shaped TiB whiskers in the titanium alloy is 1.04%-3.01%.

[0035] Compared with the prior art in which short rod-shaped TiB whiskers are easily segregated at grain boundaries, the present invention controls the area ratio and size of the short rod-shaped TiB whiskers so that small-sized short rod-shaped TiB whiskers are randomly dispersed in the initial β crystals and at the grain boundaries. Therefore, the short rod-shaped TiB whiskers provided by the present invention significantly improve the strength of titanium alloys.

[0036] Preferably, the aspect ratio of the nearly equiaxed α phase is between 1.9 and 3.9.

[0037] Preferably, the initial β crystals of the titanium alloy are equiaxed along the printing direction.

[0038] The present invention adds an appropriate amount of Fe element so that the residual β phase is equiaxial along the printing direction, which is beneficial to the isotropy of the mechanical properties of the titanium alloy provided by the present invention.

[0039] On the other hand, the present invention also provides a method for preparing the titanium alloy based on laser energy density control of phase structure, comprising:

[0040] (1) preparing raw material powder according to the mass percentage of each component of the titanium alloy for phase structure regulation based on laser energy density, ball milling, drying and cooling to obtain mixed powder;

[0041] (2) Clean and dry the TC4 material substrate, and use the laser additive manufacturing process to print the mixed powder on the TC4 material substrate. The laser power is 500-600 W and the scanning speed is 800-900 mm / min;

[0042] Alternatively, the laser power was 800-900 W and the scanning speed was 700-800 mm / min;

[0043] Alternatively, the laser power was 900-1000 W and the scanning speed was 550-600 mm / min;

[0044] Alternatively, the laser power is 1000-1100 W and the scanning speed is 500-550 mm / min.

[0045] Preferably, step (1) comprises the following steps:

[0046] The powder preparation process includes: powder weighing preparation, ball milling and mixing 3 wt.% Fe powder and 0.05 wt.% B powder with TC4 powder, wherein both Fe powder and TC4 powder are spherical powders with a particle size of 50-150 um, and the size of B powder is 50 nm. Ball milling and mixing powder, using 316L steel balls with a diameter of 5 mm as ball milling beads, the mass ratio of mixed powder to steel balls is 2:5, the ball milling speed is 200 r / min, and the ball milling time is 5 h, so that B powder is evenly attached to the surface of Fe and TC4 spherical powders, and the sphericity of Fe and TC4 spherical powders is not affected. The mixed powder is dried in a vacuum drying oven, vacuumed, and heated to 120°C, kept warm for 4 h, cooled to room temperature, and taken out for direct printing.

[0047] Preferably, the TC4 material substrate includes a single-pass printing substrate and a bulk sample printing substrate;

[0048] The single-pass printing substrate is a small substrate with a length and width of 10*10 cm and a thickness of 1 cm;

[0049] The block sample printing substrate is a large substrate with a length and width of 20*10 cm and a thickness of 8 cm.

[0050] Preferably, the TC4 material substrate is first polished with sandpaper before use, then cleaned and dried with clean water and ethanol to remove surface unevenness and dirt, and then placed in the laser additive manufacturing equipment.

[0051] Preferably, the combination of laser power and scanning speed is 600 W-900 mm / min (laser energy density is 40 J / mm 2 )、800 W-700 mm / min (laser energy density is 68 J / mm 2 )、1000 W-600 mm / min(laser energy density is 100 J / mm 2 )、1000 W-500 mm / min(laser energy density is 120 J / mm 2 ).

[0052] Preferably, the path spacing of the laser scanning is set to 60% of the cross-sectional size of the single-channel molten pool; the slice layer thickness is set to 60-80% of the cross-sectional size of the single-channel molten pool; the powder feeding rate is fixed at 6 g / min; the powder feeding gas flow rate is 15 L / min, the laser spot diameter is 1 mm, and the sample is printed.

[0053] The combination of laser power and scanning speed selected in this embodiment depends on the single-channel experiment. The laser power is 500-1100 W and the scanning speed is 300-1000 mm / min for the single-channel experiment. The cross-sectional dimensions of each molten pool are measured, and four single-channel morphologies with good fusion ratios and appropriate wetting angles are selected for block printing to ensure that the printed alloy has no macroscopic defects and good density. The printing path spacing and slice layer thickness are set according to the single-channel molten pool size.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] During the laser additive manufacturing process, when the laser energy density is low, heat is not easily transferred to other layers, resulting in a faster cooling rate for a single sheet layer, thereby forming needle-shaped α′ martensite, and further forming a titanium alloy with higher strength and relatively poor plasticity. As the laser energy density increases, the heat transferred to other layers increases, resulting in a decrease in the cooling rate of a single sheet layer, an increase in the size of the α phase, and a gradual transformation from needle-shaped α′ martensite to lath-shaped α phase, with decreased strength and increased plasticity. When the laser energy is increased to the upper limit provided by the present invention, a nearly equiaxed α phase is formed. Since the size of the α phase does not change much, the strength and plasticity changes are not obvious. The present invention can achieve a change in the morphology of the α phase by simply adjusting the laser energy density to optimize the alloy properties, thereby obtaining a titanium alloy with the required high plasticity. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1Secondary electron (SE) microstructure diagram of the titanium alloy block prepared in Examples 1 to 4 of the present application and Comparative Example 1 at the same magnification;

[0057] Figure 2 A statistical chart of the thickness of α laths in the titanium alloy blocks prepared in Examples 1 to 4 of the present application and Comparative Example 1;

[0058] Figure 3 The low-magnification secondary electron (SE) microstructure image and the optical microscope image along the printing direction of the titanium alloy block prepared in Example 4 and Comparative Example 1 of the present application;

[0059] Figure 4 XRD diagram of the titanium alloy block prepared in Examples 1 to 4 of the present application and Comparative Example 1;

[0060] Figure 5 This is a diagram of the mechanical properties of the titanium alloy blocks prepared in Examples 1 to 4 of the present application and Comparative Example 1. DETAILED DESCRIPTION

[0061] The following will provide a clear and complete description of the technical solutions in the embodiments of the present application in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.

[0062] In the existing technology, adding elements with large Q (growth limiting factor) values ​​to the alloy can increase the solute supercooling range, promote the formation of crystal nuclei, and then promote grain refinement, realize the transformation of coarse columnar crystals to equiaxed crystals along the printing direction, and improve the anisotropy of the organization and mechanical properties. Introducing ceramic reinforcement phases into the metal matrix is ​​also one of the effective methods to improve mechanical properties, but excessive addition will increase the size of the ceramic reinforcement phase and easily aggregate at the grain boundaries, hindering the coordinated deformation of the matrix and causing the plasticity of the material to drop rapidly. Therefore, the amount of ceramic reinforcement phase added needs to be strictly controlled.

[0063] The alloy composition used in the embodiment of the present invention is Ti6Al4V3Fe0.05B ​​(nominal composition), wherein the addition of Fe element and trace B element plays a role in grain refinement, transformation of columnar crystals to equiaxed crystals along the printing direction, and second phase strengthening of the ceramic reinforcement phase, thereby improving the strength and isotropy of the alloy.

[0064] Embodiment 1:

[0065] TC4 powder, Fe powder and B powder were obtained as powder raw materials for laser metal deposition, wherein the particle sizes of TC4 powder and Fe powder were 45-150 μm, and the particle size of B powder was 50 nm.

[0066] The mass of TC4 powder is 193.9 g, the mass of Fe powder is 6 g, accounting for 3 wt.%, and the mass of B powder is 0.1 g, accounting for 0.05 wt.%. A 316 L steel ball with a diameter of φ5 mm is placed in a stainless steel ball mill. The mass ratio of the steel ball to the alloy powder is 5:2. Then the mixed powder is placed in a stainless steel ball mill for ball milling. The speed of the ball mill is 200 r / min and the ball milling time is 5 h.

[0067] Use a 100-mesh sieve to separate the mixed powder after ball milling and the steel ball sieve, put the mixed powder into a bottle, seal it with perforated tin foil, put it into a vacuum drying oven, evacuate it, set the drying temperature to 120 °C, and the drying time to 4 hours. After drying, cool the powder to room temperature, then take it out and directly load it into the powder feeder for printing.

[0068] Take a 20*10 cm TC4 substrate with a thickness of 8 mm, polish the surface with sandpaper, clean it with clean water and ethanol, and dry it to remove the surface unevenness and dirt, and then put it into the laser additive manufacturing equipment.

[0069] The laser power of laser metal deposition was set to 600 W and the scanning speed was set to 900 mm / min, that is, the laser energy density was 40 J / mm 2 According to the single-channel molten pool size, the path spacing was set to 0.98 mm, the slice layer thickness was 0.25 mm, and the powder feeding rate was fixed to 6 g / min to prepare a multi-channel and multi-layer titanium alloy block without macro cracks.

[0070] Embodiment 2:

[0071] TC4 powder, Fe powder and B powder were obtained as powder raw materials for laser metal deposition, wherein the particle sizes of TC4 powder and Fe powder were 45-150 μm, and the particle size of B powder was 50 nm.

[0072] The mass of TC4 powder is 193.9 g, the mass of Fe powder is 6 g, accounting for 3 wt.%, and the mass of B powder is 0.1 g, accounting for 0.05 wt.%. A 316 L steel ball with a diameter of φ5 mm is placed in a stainless steel ball mill. The mass ratio of the steel ball to the alloy powder is 5:2. Then the mixed powder is placed in a stainless steel ball mill for ball milling. The speed of the ball mill is 200 r / min and the ball milling time is 5 h.

[0073] Use a 100-mesh sieve to separate the mixed powder after ball milling and the steel ball sieve, put the mixed powder into a bottle, seal it with perforated tin foil, put it into a vacuum drying oven, evacuate it, set the drying temperature to 120 °C, and the drying time to 4 hours. After drying, cool the powder to room temperature, then take it out and directly load it into the powder feeder for printing.

[0074] Take a 20*10 cm TC4 substrate with a thickness of 8 mm, polish the surface with sandpaper, clean it with clean water and ethanol, and dry it to remove the surface unevenness and dirt, and then put it into the laser additive manufacturing equipment.

[0075] The laser power of laser metal deposition was set to 800 W and the scanning speed was set to 700 mm / min, that is, the laser energy density was 68 J / mm 2 According to the single-channel molten pool size, the path spacing was set to 1.27 mm, the slice layer thickness was 0.4 mm, and the powder feeding rate was fixed to 6 g / min, and a multi-channel and multi-layer titanium alloy block without macro cracks was prepared.

[0076] Embodiment 3:

[0077] TC4 powder, Fe powder and B powder were obtained as powder raw materials for laser metal deposition, wherein the particle sizes of TC4 powder and Fe powder were 45-150 μm, and the particle size of B powder was 50 nm.

[0078] The mass of TC4 powder is 193.9 g, the mass of Fe powder is 6 g, accounting for 3 wt.%, and the mass of B powder is 0.1 g, accounting for 0.05 wt.%. A 316 L steel ball with a diameter of φ5 mm is placed in a stainless steel ball mill. The mass ratio of the steel ball to the alloy powder is 5:2. Then the mixed powder is placed in a stainless steel ball mill for ball milling. The speed of the ball mill is 200 r / min and the ball milling time is 5 h.

[0079] Use a 100-mesh sieve to separate the mixed powder after ball milling and the steel ball sieve, put the mixed powder into a bottle, seal it with perforated tin foil, put it into a vacuum drying oven, evacuate it, set the drying temperature to 120 °C, and the drying time to 4 hours. After drying, cool the powder to room temperature, then take it out and directly load it into the powder feeder for printing.

[0080] Take a 20*10 cm TC4 substrate with a thickness of 8 mm, polish the surface with sandpaper, clean it with clean water and ethanol, and dry it to remove the surface unevenness and dirt, and then put it into the laser additive manufacturing equipment.

[0081] The laser power of laser metal deposition was set to 1000 W and the scanning speed was set to 600 mm / min, that is, the laser energy density was set to 100 J / mm 2 According to the single-channel molten pool size, the path spacing was set to 1.53 mm, the slice layer thickness was 0.52 mm, and the powder feeding rate was fixed to 6 g / min to prepare a multi-channel and multi-layer titanium alloy block without macro cracks.

[0082] Embodiment 4:

[0083] TC4 powder, Fe powder and B powder were obtained as powder raw materials for laser metal deposition, wherein the particle sizes of TC4 powder and Fe powder were 45-150 μm, and the particle size of B powder was 50 nm.

[0084] The mass of TC4 powder is 193.9 g, the mass of Fe powder is 6 g, accounting for 3 wt.%, and the mass of B powder is 0.1 g, accounting for 0.05 wt.%. A 316 L steel ball with a diameter of φ5 mm is placed in a stainless steel ball mill. The mass ratio of the steel ball to the alloy powder is 5:2. Then the mixed powder is placed in a stainless steel ball mill for ball milling. The speed of the ball mill is 200 r / min and the ball milling time is 5 h.

[0085] Use a 100-mesh sieve to separate the mixed powder after ball milling and the steel ball sieve, put the mixed powder into a bottle, seal it with perforated tin foil, put it into a vacuum drying oven, evacuate it, set the drying temperature to 120 °C, and the drying time to 4 hours. After drying, cool the powder to room temperature, then take it out and directly load it into the powder feeder for printing.

[0086] Take a 20*10 cm TC4 substrate with a thickness of 8 mm, polish the surface with sandpaper, clean it with clean water and ethanol, and dry it to remove the surface unevenness and dirt, and then put it into the laser additive manufacturing equipment.

[0087] The laser power of laser metal deposition was set to 1000 W and the scanning speed was set to 500 mm / min, that is, the laser energy density was set to 120 J / mm 2 According to the single-channel molten pool size, the path spacing was set to 1.68 mm, the slice layer thickness was 0.52 mm, and the powder feeding rate was fixed to 6 g / min to prepare a multi-channel and multi-layer titanium alloy block without macro cracks.

[0088] Comparative Example 1: The additive manufacturing process is the same as that of Example 4, except that Fe powder and B powder are not added in the comparative example.

[0089] See also Figure 1 , Figure 1 The tissue morphology diagrams of Examples 1 to 4 and Comparative Example 1 are shown. Figure 1 (a) is the microstructure morphology of the titanium alloy block prepared in Example 1. 2 When , the α phase in the alloy is mainly composed of needle-shaped α′ martensite phase; Figure 1 (b) is the microstructure morphology of the titanium alloy block prepared in Example 2. 2 When , the α phase in the alloy is composed of needle-shaped α′ martensite and lath-shaped α; Figure 1(c) is the microstructure morphology of the titanium alloy block prepared in Example 3. 2 When , the α phase in the alloy is mainly composed of lath-shaped α; Figure 1 (d) is a microstructure morphology of the titanium alloy block prepared in Example 4, and the α phase in the alloy is mainly composed of a nearly equiaxed α phase; Figure 1 (e) is a microstructural morphology of the titanium alloy block prepared in Comparative Example 1, which is mainly composed of coarser lath-like α phase.

[0090] It can be seen that the laser energy density has a great influence on the morphology of the α phase in the alloy, because different laser energy densities correspond to different cooling rates. When the laser energy density is low, the layer-by-layer heat accumulation effect during the printing process is not obvious, the block cools faster, and tends to form a fine needle-shaped martensite phase. When the laser energy density is high, it will cause higher heat accumulation, which will reduce the cooling rate of the alloy and make the alloy more likely to form coarse lath-shaped or nearly equiaxed α. Due to the smaller solidification range of TC4 alloy and the lack of nucleus incubation and growth time, its lath-shaped structure is coarser than that of Ti6Al4V3Fe0.05B ​​alloy.

[0091] See also Figure 2 , Figure 2 The statistical graph of the thickness of the α-slats of Examples 1 to 4 and Comparative Example 1 is shown. Figure 2 (a) is a statistical diagram of the thickness of the α lath of Example 1; Figure 2 (b) is a statistical diagram of the thickness of the α lath of Example 2; Figure 2 (c) is a statistical diagram of the thickness of the α lath of Example 3; Figure 2 (d) is a statistical diagram of the thickness of the α lath of Example 4; Figure 2 (e) is the statistical diagram of the α lath thickness of comparative example 1. It can be seen that the laser energy density has a significant effect on the size of the lath. With the increase of laser energy density, the thickness of the α phase in the Ti6Al4V3Fe0.05B ​​alloy shows a gradual upward trend. The laser energy density is 40J / mm 2 When the laser energy density is 68 J / mm 2 When the laser energy density is 100 J / mm 2 When the laser energy density is 120 J / mm 2 When the laser energy density is 120 J / mm, the average thickness of the nearly equiaxed α phase is about 233 nm. 2When the cooling rate of the alloy is 0.1447 W, the average thickness of the α phase is about 377 nm. It can be seen that the laser energy density affects the cooling rate of the alloy, which plays a role in regulating the morphology and size of the α phase of the titanium alloy, and the design of the alloy composition realizes the refinement of the alloy phase size.

[0092] See also Figure 3 , Figure 3 The low-magnification microstructure diagram and the structure diagram along the printing direction of Comparative Example 1 and Example 4 are shown. Figure 3 (a) shows a low-magnification SE image of the microstructure of Comparative Example 1. Figure 3 (b) shows the low-magnification microstructure SE image of Example 4. It can be seen that after adding a trace amount of B element, dispersed TiB reinforcement exists in the titanium alloy matrix. Figure 3 (c) shows the microscopic image of the structure of comparative example 1 along the printing direction, and it can be clearly seen that the coarse columnar crystals formed along the printing direction. Figure 3 (d) shows the optical microscopic image of the structure of Example 4 along the printing direction. It can be seen that after the addition of Fe and B elements, the coarse columnar crystals along the printing direction are transformed into equiaxed crystals, which will also improve the isotropy of the mechanical properties of the alloy.

[0093] See also Figure 4 , Figure 4 The XRD curves of Examples 1 to 4 and Comparative Example 1 are shown, wherein Ti6Al4V3Fe0.05B ​​E = 40 J / mm 2 XRD curve of Example 1; Ti6Al4V3Fe0.05B ​​E = 68 J / mm 2 XRD curve of Example 2; Ti6Al4V3Fe0.05B ​​E = 100 J / mm 2 XRD curve of Example 3; Ti6Al4V3Fe0.05B ​​E = 120 J / mm 2 XRD curve of Example 4; Ti6Al4V E = 120 J / mm 2 This is the XRD curve of comparative example 1. The β phase peak intensity represented by 39.5° in the Ti6Al4V (TC4) alloy is relatively low, indicating that the alloy contains a small amount of β phase. After adding the β-stabilizing element Fe, the β phase region is expanded, so that more β phases are retained without undergoing phase transformation after the solidification process, and an increase in the β phase peak intensity at 39.5° is observed. However, at this time, the main matrix phase of the alloy is still the α phase, and different laser energy densities have no significant effect on the phase composition in the Ti6Al4V3Fe0.05B ​​alloy.

[0094] See also Figure 5 , Figure 5The engineering stress-strain curves of Examples 1 to 4 and Comparative Example 1 are shown. Curve 1 is the engineering stress-strain curve of Example 1; Curve 2 is the engineering stress-strain curve of Example 2; Curve 3 is the engineering stress-strain curve of Example 4; Curve 4 is the engineering stress-strain curve of Example 3; Curve 5 is the engineering stress-strain curve of Comparative Example 1. As shown in the figure, the Ti6Al4V3Fe0.05B ​​alloy has a laser energy density of 40 J / mm 2 When the tensile strength of the alloy is 1592 MPa, the plastic elongation at fracture is 3.4%; the laser energy density is 68 J / mm 2 When the tensile strength of the alloy is 1527MPa, the plastic elongation at fracture is 5.3%; the laser energy density is 100 J / mm 2 When the tensile strength of the alloy is 1411 MPa, the plastic elongation at fracture is 11.6%; the laser energy density is 120 J / mm 2 When the laser energy density is 120 J / mm 2 The tensile strength is 1098MPa and the plastic elongation at fracture is 9.3%. It can be seen that after adding Fe and trace B elements, the tensile strength of titanium alloy has been greatly improved. By adjusting the laser energy density, a series of alloys with different mechanical properties have been obtained. 2 When the titanium alloy is used in the production process, the strength and plasticity of the titanium alloy are better matched. Compared with the TC4 alloy, the strength is significantly improved while the elongation of the material does not decrease.

[0095] The embodiment of the present invention realizes the regulation of the morphology and size of the α phase in the designed alloy Ti6Al4V3Fe0.05B ​​by regulating the laser energy density during the additive manufacturing process, and further realizes the improvement of the alloy strength and the matching of strength and plasticity. The Fe element is added to the TC4 alloy, which plays a role in refining the grains, and promotes the transformation of columnar crystals to equiaxed crystals along the printing direction, thereby improving the isotropy of the alloy strength and mechanical properties. A trace amount of B element is added to the TC4 alloy, and B and Ti in situ self-generate needle-shaped TiB reinforcements during the laser melting process, which are dispersed inside the grains and at the grain boundaries. The high melting point TiB acts as a heterogeneous nucleation site to promote grain refinement, TiB pins dislocations, and improves the strength of the alloy. At the same time, it also plays a role in transferring the matrix load and improving the plasticity of the alloy. Furthermore, when the laser energy density is low, the layer-by-layer heat accumulation effect during the printing process is not obvious, the block cooling rate is faster, and it tends to form a fine needle-shaped martensite phase, the alloy has high strength, and the plasticity is poor. When the laser energy density is high, it will cause higher heat accumulation, which will reduce the cooling rate of the alloy, and the alloy will be more likely to form thick lath-shaped or nearly equiaxed α, the alloy plasticity will be improved, and the strength will be slightly reduced, achieving a good match between the strength and plasticity of the alloy. In addition, the preparation method provided by the present invention is universal, and the preparation process is simple, the production cycle is short, and the repeatability is high, and it can be extended to other dual-phase titanium alloys.

Claims

1. A titanium alloy with phase structure regulated by laser energy density, characterized in that: The mass percentages of the components of the titanium alloy include Al: 5.54%-6.68%, V: 4.25%-4.48%, Fe: 2.59%-3.04%, B: 0.02-0.08%, and the balance is Ti; The titanium alloy matrix is ​​mainly composed of an α phase and a residual β phase. The titanium alloy is obtained by laser additive manufacturing. Under different laser energy densities, the α phase includes needle-shaped α′ martensite, needle-shaped α′ martensite+lath-shaped α phase, lath-shaped α phase or nearly equiaxed α phase; As the laser energy density increases, the α phase undergoes the following changes in sequence: Needle-shaped α′ martensite → needle-shaped α′ martensite + lath-shaped α phase → lath-shaped α phase → nearly equiaxed α phase; When the laser energy density is 33-45 J / mm 2 When , the α phase is mainly composed of needle-shaped α′ martensite; When the laser energy density is 60-77 J / mm 2 When the α phase includes needle-shaped α′ martensite and lath-shaped α phase, the area ratio of the needle-shaped α′ martensite to the lath-shaped α phase is 0.21-0.39; When the laser energy density is 90-109 J / mm 2 109 J / mm is not included 2 , the α phase is mainly composed of lath-shaped α phase; When the laser energy density is 109-132 J / mm 2 When α phase is mainly composed of nearly equiaxed α phase.

2. The titanium alloy with phase structure regulated by laser energy density according to claim 1, characterized in that: The laser energy density is 33-45 J / mm 2 , the tensile strength of the titanium alloy is 1592-1610 MPa, and the plasticity of the titanium alloy is 3.4-3.9%; The laser energy density is 60-77 J / mm 2 , the tensile strength of the titanium alloy is 1502-1574 MPa, and the plasticity of the titanium alloy is 4.8-5.6%; The laser energy density is 90-109 J / mm 2 , the tensile strength of the titanium alloy is 1324-1415 MPa, and the plasticity of the titanium alloy is 9.4-11.7%; The laser energy density is 109-132 J / mm 2 The tensile strength of the titanium alloy is 1359-1451 MPa, and the plasticity of the titanium alloy is 11.1-11.7%.

3. The titanium alloy with phase structure controlled by laser energy density according to claim 1, characterized in that: The laser energy density is 33-45 J / mm 2 , the thickness of the α phase is 55-91 nm; The laser energy density is 60-77 J / mm 2 , the thickness of the α phase is 78-182 nm; The laser energy density is 90-109 J / mm 2 , the thickness of the α phase is 175-285 nm; The laser energy density is 109-132 J / mm 2 , the thickness of the α phase is 203-328 nm.

4. The titanium alloy with phase structure controlled by laser energy density according to claim 1, characterized in that: The titanium alloy is a basketweave structure and includes in-situ self-generated short rod-shaped TiB whiskers. The size of the short rod-shaped TiB whiskers is less than 1 μm and is randomly dispersed in the initial β crystals and at the grain boundaries.

5. The titanium alloy with phase structure regulated by laser energy density according to claim 1, characterized in that: The aspect ratio of the nearly equiaxed α phase is between 1.9 and 3.

9.

6. The titanium alloy with phase structure controlled by laser energy density according to claim 1, characterized in that: The initial β crystals of the titanium alloy are equiaxed along the printing direction.

7. A titanium alloy based on laser energy density control of phase structure according to any one of claims 1 to 6, characterized in that: include: (1) preparing raw material powders according to the mass percentage of each component of the titanium alloy for phase structure regulation based on laser energy density according to any one of claims 1 to 6, ball milling, drying and cooling to obtain mixed powder; (2) Clean and dry the TC4 material substrate, and use the laser additive manufacturing process to print the mixed powder on the TC4 material substrate. The laser power is 500-600 W and the scanning speed is 800-900 mm / min; Alternatively, the laser power was 800-900 W and the scanning speed was 700-800 mm / min; Alternatively, the laser power was 900-1000 W and the scanning speed was 550-600 mm / min; Alternatively, the laser power is 1000-1100 W and the scanning speed is 500-550 mm / min.

Citation Information

Patent Citations

  • Nanocrystalline structure Ti6Al4V-Ag alloy and additive manufacturing preparation method thereof

    CN112251640A

  • Method for inhibiting formation of acicular martensite phase in TC4 alloy structure by 3D printing

    CN110983106A